Research progress on lacrimal duct stent materials - TANG Yan; ZHANG Yongxin; YE Lin (Yanke Xuebao)
Lacrimal duct obstruction is a common clinical ophthalmic condition characterized by symptoms such as epiphora and recurrent infections, significantly impairing patients' quality of life. Traditional treatments primarily involve the implantation of silicone or metal stents. While these materials can temporarily maintain lacrimal duct patency, their inherent drawbacks—such as non-degradability, susceptibility to displacement, and tendency to form biofilms leading to infections—often necessitate secondary surgeries for removal, imposing additional physical and financial burdens on patients.Advances in materials science and biomedical engineering have introduced novel stent materials as potential solutions to these challenges. This article focuses on emerging materials such as biodegradable polymers, 3D-printed personalized stents, composite materials, and surface modification technologies. These innovations can enhance clinical outcomes through material degradation, precise customization, or multifunctional integration. However, challenges remain in regulating degradation rates, improving 3D printing precision, and reducing costs.Furthermore, the long-term safety and efficacy of these technologies require more clinical data for validation. Future research should explore more precise degradation rate control methods, optimize 3D printing processes to enhance accuracy, lower material production costs, and develop more efficient composite material fabrication techniques. Concurrently, strengthening fundamental research and promoting the clinical application of innovative technologies will be crucial to developing safer and more effective lacrimal duct stent materials. Such advancements will provide superior treatment options for patients with lacrimal duct obstruction and drive the field toward minimally invasive and precision medicine approaches.